Rancang Bangun Sistem Informasi Geografis Kependudukan di Dinas Kependudukan dan Pencatatan Sipil Kota Mataram - Muamar Ikhsan; Ida Bagus Ketut Widiartha; Nadiyasari Agitha (Journal of Computer Science and Informatics Engineering (J-Cosine), 2018)
Department of Population and Civil Registration of Mataram City does not yet have a system that can process population data to be visualized into maps and lack of information causing people not to know information about the area and population data in Mataram city. This study aims to design and build a Geographic Information System (GIS) that is useful to visualize and publish population data to the community in the city of Mataram. The system is built using PHP, HTML and JavaScript as the main programming language. The system integrates with the Google Map API to visualize population data into maps that provide information by population classification. The system is tested by the BlackBox method and the MOS (Mean Opinion Score) method. Blackbox test shows that all functions are running well and testing using MOS shows that the average rating of respondents and community apparatus in DUKCAPIL regarding the system agree, with the percentage of 42.44% and strongly agree with the percentage of 38.89%.